2012
DOI: 10.1007/s11270-012-1301-7
|View full text |Cite
|
Sign up to set email alerts
|

Winter Time Concentrations and Size Distribution of Bioaerosols in Different Residential Settings in the UK

Abstract: The total concentration and size distribution of bioaerosols in three different types of housing (single room in shared accommodation (type I), single bedroom flat in three storey building (type II) and two or three bedroom detached houses (type III)) was assessed during the winter. This research was an extension of a previous study carried out in the summer. The measurement campaign was undertaken in winter 2008 and thirty houses were sampled. Samples were taken from kitchens, living rooms, corridors (only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…All homes are in 1 to 22 story buildings, with 8 homes in low story (1-3), 14 homes in middle story (4-10), and 8 homes in high story (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The urban districts included Xuanwu (n = 4), Gulou (n = 3), Qinhuai (n = 1), and Jianye (n = 3), and the suburban districts included Jiangning (n = 9), Qixia (n = 6), and Pukou (n = 4), shown in Figure 1.…”
Section: Sampling Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…All homes are in 1 to 22 story buildings, with 8 homes in low story (1-3), 14 homes in middle story (4-10), and 8 homes in high story (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The urban districts included Xuanwu (n = 4), Gulou (n = 3), Qinhuai (n = 1), and Jianye (n = 3), and the suburban districts included Jiangning (n = 9), Qixia (n = 6), and Pukou (n = 4), shown in Figure 1.…”
Section: Sampling Protocolmentioning
confidence: 99%
“…Residential bioaerosols have been extensively studies around the world, including developed countries like United States, 9,10 Denmark, 11 Australia, 12 UK, 13 and Korea, 14,15 as well as developing countries like China 16,17 and Pakistan 18 . Previous studies have reported that indoor spaces often harbor unique microbial communities, with common bacteria in indoor environments being Staphylococcus , Corynebacterium , Lactococcus , Firmicutes , and Actinobacteria 1,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Outdoor bacteria and fungi from plants and vegetables 25 can enter the building through ventilation systems, doors, windows, attached to people, pets, and other objects, as a result, affecting the indoor concentration level. 26 However, information on these factors is still not well understand. The indoor and outdoor influencing factors need to be systematically considered to make recommendations for microbes controlling.…”
Section: Introductionmentioning
confidence: 99%
“…As the primary source, a human can emit about 14 million cells h ‐1 for bacteria and 14 million spore equivalents h ‐1 for fungi, which cause the average airborne bacteria to reach 81 times and fungi to reach 15 times concentrations as compared to vacant classrooms 24 . Outdoor bacteria and fungi from plants and vegetables 25 can enter the building through ventilation systems, doors, windows, attached to people, pets, and other objects, as a result, affecting the indoor concentration level 26 . However, information on these factors is still not well understand.…”
Section: Introductionmentioning
confidence: 99%
“…A range of factors including ventilation, building design, management and usage can greatly affect the bioaerosols levels in hospitals. These factors vary across the globe due to socioeconomic and climatic conditions [13]. In Pakistan, infection control strategies and their applications are highly variable across the health settings.…”
Section: Introductionmentioning
confidence: 99%